2020
DOI: 10.24251/hicss.2020.613
|View full text |Cite
|
Sign up to set email alerts
|

Developing Intellectual Capital in Professional Service Firms Using High Performance Work Practices as Toolkit

Abstract: The role of Professional Service Firms (PSFs) has always been crucial in the development of knowledge economies. The effectiveness of these firms is highly attributed to the knowledge capabilities and skills embedded in its human resources and how effectively these resources are utilized in the optimal benefit of the firm. Owing to the ever-increasing growth of the services sector globally, it's critical for the PSFs to gain in-depth awareness on the application of High-Performance-Work-Practices (HPWPs) so as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 54 publications
2
9
0
Order By: Relevance
“…Mentioning trust, IS professionals said that (1) "A good working environment contributes to better individual performance, as the employee does not feel inhibited from sharing information," (2) "Team members must be aware of the work they need to do and should know with whom they can count on for help" and (3) "A good atmosphere helps [the individual] to be more enthusiastic and relaxed, feeling less pressure about the work that is being done." This is in line with previous research (Lencioni, 2002;Weimar et al, 2013;Rehman et al, 2020). The following quotes: (1) "If a person feels good doing the job then the latter will be done with will and better quality," and (2) "Motivation makes us [as individuals] more focused on the tasks at hand because it increases the levels of confidence about work done and, consequently, the responsibility for that same work" illustrate that the IS project teams' productivity and the quality of team products depend on team members being motivated and satisfied with their job (Sudhakar et al, 2011;Weimar et al, 2013;Leonard and van Zyl, 2014).…”
Section: Management/ Leadershipsupporting
confidence: 94%
See 3 more Smart Citations
“…Mentioning trust, IS professionals said that (1) "A good working environment contributes to better individual performance, as the employee does not feel inhibited from sharing information," (2) "Team members must be aware of the work they need to do and should know with whom they can count on for help" and (3) "A good atmosphere helps [the individual] to be more enthusiastic and relaxed, feeling less pressure about the work that is being done." This is in line with previous research (Lencioni, 2002;Weimar et al, 2013;Rehman et al, 2020). The following quotes: (1) "If a person feels good doing the job then the latter will be done with will and better quality," and (2) "Motivation makes us [as individuals] more focused on the tasks at hand because it increases the levels of confidence about work done and, consequently, the responsibility for that same work" illustrate that the IS project teams' productivity and the quality of team products depend on team members being motivated and satisfied with their job (Sudhakar et al, 2011;Weimar et al, 2013;Leonard and van Zyl, 2014).…”
Section: Management/ Leadershipsupporting
confidence: 94%
“…One of the IS professionals stated that: "Workers have to be payed a salary in accordance with the work they do and with the labor market." Rewarding high-performing employees (with prestige and advantage opportunities (Klaus et al, 2014)) can influence individual behavior and workrelated performance (Rehman et al, 2020). Differentiated employee compensation strategies 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The burgeoning literature advocated that organizations following HPWPs indicated improved motivation, high-quality services, products, increased innovative task behaviors, creativity, job crafting, efficiency, low levels of absenteeism, and turnover of employees (Kim et al, 2015;Messersmith et al, 2018;Ali et al, 2019;Chughtai and Rizvi, 2019;Aeknarajindawat et al, 2020;He et al, 2021;Li et al, 2021). Additionally, HPWPs augment the skills, capabilities, and intellectual capital of employees, especially in service industries (Ali et al, 2018;Rehman et al, 2020). Recent studies revealed the influential role of HPWPs in human resource management strategies in Western culture; however, limited studies have explored its impact on developing economies (Cooke, 2018;Cooke et al, 2019).…”
Section: High-performance Work Practices Eirp and Etpmentioning
confidence: 99%